(untitled) (Journal of the College of Basic Education, 2022)
The study included 50 samples collected from the stool of children with bloody diarrhea and acute watery and were aged under five years of age, if possible, get a 14 bacterial isolates out of 50 samples and 28%, while the samples where growth does not appear, which were represented by 72% of the total samples may be due to the presence of other pathogens that causes it may be sick from parasites such as Entamoeba histolytica, and Giardia Lamblia and Crytosporidium Parvum and Cayetanensi Cyclospora, or may be due occurrence of diarrhea to the presence of viruses, especially rotavirus which is one of the most viral common types and causes of diarrhea among children under the age of five years, as the bacteria E.coli accounted for the highest percentage, bringing the total isolation of 10 at a rate of 20% of the total samples, either Salmonella bacteria have been getting the isolation of a single 2% of the total samples, and the other was to get three isolates belonging to the bacteria Shigella 21.4% of the total isolates Separation of lactoferrin protein from colostrum cows from cows type) Friesen) in the first week after birth in order to study its ability to inhibit the bacterium that causes the growth of diarrhea under hometown, the results showed the efficiency of the effect of the protein lactoferrin in inhibiting bacteria Salmonella outside the body of the organism and amounted to inhibition zone up to 15 mm and injury rates have decreased in mice when using the protein lactoferrin in vivo.